Pengaruh Pelatihan, Disiplin Kerja, dan Kepuasan Kerja terhadap Kinerja Karyawan pada Kantor SAMSAT Jakarta Barat - Masyitoh, Rizka Nur (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
This study aims to determine the effect of Training, Work Discipline, and Job Satisfaction on Performance of employees West Jakarta SAMSAT Office. The object of research on job satisfaction as the dependent variable and the independent variables are Training, Work environment and Job Satisfaction. This research was conducted on 75 using a quantitative descriptive approach and saturated sampling. Methods of data analysis is Structural Equation Model (SEM) dan Smart Partial Least Square (PLS) The result of this research that (1) Training has a positif and significant effect Employee Performance, (2) Work Discipline has a positif and significant effect on Employee Performance and (3) Job Satisfaction has a positive and significant effect on employee Performance